2016
DOI: 10.1186/s13039-015-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

Somatic/gonadal mosaicism for structural autosomal rearrangements: female predominance among carriers of gonadal mosaicism for unbalanced rearrangements

Abstract: BackgroundMosaicism for chromosomal structural rearrangements (Rea) is rare and the timing and mechanisms of mosaic Rea formation, maintenance, and clinical manifestation are poorly understood. To date, there are no published data on the cytogenetic profile of mosaic Reas. The question as to whether the proportion of abnormal cells in the carrier’s cultured blood is clinically significant remains unanswered. A previous study showed a strong female preponderance among carriers of mosaicism for Rea with pericent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 106 publications
1
13
0
Order By: Relevance
“…Balanced Rea (reciprocal translocations and inversions) were not included in the analysis, comprising 51% of the cases in asymptomatic carriers [2]. Of the remaining 203 cases, there were 65 deletions (32%), 39 duplications (19%), 48 rings (24%), 23 unbalanced translocations (11%), and 28 other Reas (14%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balanced Rea (reciprocal translocations and inversions) were not included in the analysis, comprising 51% of the cases in asymptomatic carriers [2]. Of the remaining 203 cases, there were 65 deletions (32%), 39 duplications (19%), 48 rings (24%), 23 unbalanced translocations (11%), and 28 other Reas (14%).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study of patients with somatic/gonadal mosaicism described differences in cytogenetic profile among asymptomatic and affected individuals [2]. In addition, the study revealed a strong female prevalence among both affected and asymptomatic carriers of somatic/gonadal mosaicism for unbalanced Rea, unlike the typical male prevalence among carriers of balanced Rea.…”
Section: Introductionmentioning
confidence: 98%
“…Mosaicism for structural chromosomal rearrangements is extremely rare, detected in 0.002/1,000 patients with reproductive failure [Kovaleva and Cotter, 2016]. Asymptomatic carriers of non-centromeric rearrangements with affected children were evaluated in a study, and among them 33 of 42 were found to be mosaic for an unbalanced rearrangement including 16 ring chromosomes, 8 duplications, 4 unbalanced translocations, and 5 other rearrangements [Kovaleva and Cotter, 2016]. It has also been reported that the prevalence of asymptomatic carriers of an unbalanced rearrangement is more common in females due to male-specific selection against abnormal cells [Kovaleva and Cotter, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic carriers of non-centromeric rearrangements with affected children were evaluated in a study, and among them 33 of 42 were found to be mosaic for an unbalanced rearrangement including 16 ring chromosomes, 8 duplications, 4 unbalanced translocations, and 5 other rearrangements [Kovaleva and Cotter, 2016]. It has also been reported that the prevalence of asymptomatic carriers of an unbalanced rearrangement is more common in females due to male-specific selection against abnormal cells [Kovaleva and Cotter, 2016]. Gonadal mosaicism in unbalanced chromosome abnormalities is mostly due to postzygotic mutations, but it can also originate during meiosis in trisomic zygotes by 2 parallel trisomic rescue events.…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of segmental mosaicism are also rarely found both among prenatal diagnoses [ 4 ] and among patients referred for cytogenetic testing [ 5 ]. In the general population, segmental mosaicism for balanced chromosome rearrangements (balanced translocations and inversions) and unbalanced autosome rearrangements is extremally rare, with calculated frequencies of 0.02 ‰, 0.005 ‰ respectively; segmental mosaicism for unbalanced autosomal rearrangements was reported as 0.002 ‰ [ 6 ].…”
Section: Introductionmentioning
confidence: 99%